Pengaruh Motivasi Terhadap Kinerja Karyawan Pada CV Rimba Asam Sejahtera - Noprian; Saudi Berlian; Septiadi (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2024)
The aim of this research is to determine the effect of motivation (X) on employee performance (Y) at CV Rimba Asam Sejahtera. This research uses descriptive quantitative research methods. Data collection techniques use questionnaires and documentation. The sample in this study consisted of 34 respondents by distributing questionnaires using a saturated sample, namely the entire population was used as a sample. The data analysis technique used in this research uses simple linear regression analysis with the help of SPSS data processing. The research results show that motivation variables have a positive and significant effect onemployee performance variables at CV Rimba Asam Sejahtera.